Research Trends in Local Wisdom Integrated Scaffolding Inquiry Learning Model to Improve Students' Science Literacy: Bibliometric Analysis 2014-2024 - Ferniawan Ferniawan; Agus Ramdani; Joni Rokhmat; A Wahab Jufri; AA Sukarso (Postgraduate Program, University of Mataram, 2024)
This study aims to provide a bibliometric review of research trends on local wisdom-integrated scaffolding inquiry models to improve students' scientific literacy during the period 2014-2024. Data were obtained through Google Scholar using analysis tools such as Publish or Perish and Dimension.ai, resulting in 1,000 documents selected based on PRISMA guidelines. The analysis was carried out using bibliometric and content analysis methods, supported by VOSviewer software to visualize keyword trends and research patterns. The results showed that the publication trend peaked in 2021, reflecting significant interest in this topic. The dominant publication types were chapters and edited books, indicating that this topic is often discussed in comprehensive academic references. Keywords such as local wisdom, scientific literacy, and scientific inquiry indicate the focus of research on the integration of local cultural values ​​with a scientific-based approach. Network visualization and research density underscore the importance of evaluating the effectiveness of local wisdom-based learning in improving students' scientific literacy, problem-solving skills, and scientific understanding. So it can be concluded that the research trend of the local wisdom integrated scaffolding inquiry model has become the main focus in the development of science education that is relevant and contextual to the needs of the 21st century.